A Simple and Rapid Ultra–High‐Performance Liquid Chromatography–Tandem Mass Spectrometry Method for the Quantitation of Pharmaceuticals and Related Compounds in Mussels and Oysters. (19th May 2021) - Maskrey, Benjamin H.; Dean, Karl; Morrell, Nadine; Turner, Andrew D.
Abstract: A simple, rapid ultra–high‐performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS) method has been developed and optimized for the quantitation of a range of pharmaceuticals, metabolites, and related bioactive compounds in the bivalve mollusc species mussels ( Mytilus edulis ) and Pacific oysters ( Crassostrea gigas ). Shellfish tissues were extracted using a simple solvent‐based extraction method prior to concentration and purification by pass‐through solid‐phase extraction and quantified using stable isotope dilution MS/MS. The analytes covered a range of therapeutic classes including antidepressants, anticonvulsants, beta‐blockers, and antiplatelets. Of the 34 compounds included in the present study initially, 28 compounds were found to demonstrate acceptable performance. Performance was assessed by examining extraction efficiencies, matrix effects, sensitivity, and within‐ and between‐batch precision. The results show that as indicated by acceptable HorRat and accuracy values, the method is fit for purpose. Application of this method to environmental mussel and oyster samples revealed the presence of 12 compounds at quantifiable concentrations, with the antidepressant sertraline being present at the highest level, reaching a concentration of 6.12 ng/g in mussel tissue. © 2021 Crown copyright. Environmental Toxicology and Chemistry 2021;40:3263–3274. © 2021 SETAC. This article is published with the permission of the Controller of HMSO and the Queen's Printer for Scotland.